(untitled) (Revista Científica Integrada, 2024)
Objective: To map the status of scientific production of the relationship between discriminatory algorithms and human behavior for the intensification of structural racism. Methods: A scoping review was conducted using Scopus, Embase, PubMed, and Periodicals of Capes databases between September and October 2023. The descriptors "algorithmic discrimination," "racist algorithms," and "behavior" were used. Initially, 254 articles were identified, but only 6 were selected to compose the final sample. Results: The majority were theoretical articles, all developed by/or in collaboration with authors from the United States of America, published in English between 2019 and 2023, and belonged to the fields of Philosophy, Law, Health, Economics, and Informatics. In the analysis of the articles, six relevant topics of the problem discussion were identified: (1) The importance of adopting an anti-racist stance in the development and implementation of algorithms. (2) Racial algorithmic discrimination on the typing autocorrection feature. (3) Racial algorithmic discrimination in the financial sector. (4) Racial algorithmic discrimination in the judiciary system. (5) Racial algorithmic discrimination in health. Conclusion: The majority of studies addressing this theme are in the field of law, with a predominance of North American studies, highlighting the need to expand scientific production to other areas of knowledge and promote greater cultural and geographical representativity in scientific debate.